Application of Pancasila Values in Improving Students' Creative Character in Students Class III State Elementary School 104279 Paya Itik - Sembiring, Anggi (Journal of General Education Science, 2024)
This study aims to improve students' creative character through the application of Pancasila values in the learning process for third-grade students of SD Negeri 104279 Paya Itik. This study is a Classroom Action Research (CAR). This research was conducted in two cycles. The research subjects were 10 male and 12 female third-grade students of SD Negeri 104279 Paya Itik. The research instruments used in this study were observation sheets and tests. The data analysis technique used was Classroom Action Research (CAR). The results of the study indicate that the application of Pancasila values is still considered quite effective in improving students' creative character. In the first cycle, there were 9 students who completed the course with a completion percentage of 41% and 13 students who did not complete it with a percentage of 59%. Then in the second cycle, 19 students completed the course with a percentage of 86% and 3 students who did not complete it with a percentage of 14%. The conclusion of this study is that the application of Pancasila values in learning can improve the creative character of third-grade students at SD Negeri 104279 Paya Itik. This indicates that the integration of Pancasila-based character education is very effective in shaping students who are not only knowledgeable but also creative and have noble personalities.